2014
DOI: 10.1183/09031936.00176213
|View full text |Cite
|
Sign up to set email alerts
|

Does traffic noise influence respiratory mortality?

Abstract: @ERSpublicationsA single positive Pseudomonas aeruginosa sputum culture is not associated with increased longterm mortality in COPD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Recently, two studies have specifically correlated road traffic noise with respiratory (Tobías et al, 2014a) and cardiovascular mortality (Tobías et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies have specifically correlated road traffic noise with respiratory (Tobías et al, 2014a) and cardiovascular mortality (Tobías et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex and obesity all play a role, as do upper airway anatomy/physiology [5] and control of breathing [6,7], but these traditional risk factors are all measured at an individual level rather than at a household, community or city level. Many conditions, particularly in respiratory medicine, are driven by environmental factors that may exist at a household level (tobacco smoke exposure or solid fuel heating), community level (for instance, urban noise levels [8]) or municipal/city level ( pollen counts and heatwaves). Some work has identified neighbourhood as being a risk factor for poor compliance with continuous positive airway pressure therapy [9] but very few investigators have looked at what components of a neighbourhood might increase the risks of sleep apnoea itself.…”
mentioning
confidence: 99%
“…Noise, as mentioned previously, cause not only hearing impairment but also affects multiple organ systems of human [ 19 , 47 , 53 ]. Many epidemiological studies have suggested the nonauditory effect of long-term noise low-level noise exposure, including cardiovascular disease, respiratory disease, and psychological disease [ 13 , 19 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Sleep disturbance and mental health problems are among the seven health effects and social outcomes from noise exposure confirmed by WHO [ 56 ].…”
Section: Discussionmentioning
confidence: 99%